THE DIFFERENCES IN PERCEPTION OF THE BASIC VALUE “DEVELOPMENT” IN PUBLIC LINGUISTIC COSCIOUSNESS OF RUSSIAN GENERATIONS ON THE BASIS OF ASSOCIATIVE DICTIONARIES AND THE DATA OF THE PSYCHOSEMANTIC EXPERIMENT - Zhamaletdinova, E.K. (RUDN Journal of Language Studies, Semiotics and Semantics, 2018)
This article examines the meaning of basic value “development” reflected on the common level of linguistic consciousness of representatives of two generations: the one of “perestroika” times and the Post Soviet one. The common level of linguistic consciousness is revealed through analysis of associative dictionaries and the results of the psycho-semantic experiment. The analysis of the articles from associative dictionaries helps to distinguish components of the meaning of the basic value under investigation on the common level of linguistic civil consciousness. The data of the psycho-semantic experiment that is presented as factor matrices and cluster trees allow to capture connotative differences of the perception of the value in question and trace the link with such values as “labour” and “cooperation”. We resort to historical, sociological and statistic data in order to interpret the results of the analysis. The methodology of the research is based on the theory of activity approach elaborated by Leontiev A.N., the conception of linguistic consciousness of Tarasov E.F. and Ufimtseva N.V. and the intergrative and eclectic approach by the mixed method designed by Yanchuk V.A. The results of the given research show that there were not significant shifts in the perception of the value “development” on the common level of linguistic consciousness of the two generations. However we can spotted the changes in the contents of the value in question on the linguistic common level of civil consciousness due to the movement from the industrial type of economy to the postindustrial one that is characterized by the growing significance of intellect. The methods of the analysis can be potentially used for similar research of basic values of national cultures. The materials of this paper can be employed to create tasks for Russian as Foreign language classes.